Bike-sharing and the promotion of urban sustainable mobility. A comparison of the political-aesthetic experiences provided by Vienna's Citybike and Paris' Vélib'. - Floret, Matthieu (My University, 2014)
Innerhalb des letzten Jahrzehnts hat Bike-Sharing die Straßen der Städte weltweit verändert. Durch seine Auswirkungen auf den Stadtverkehr soll der als nachhaltig individuell-kollektive Mobilitätsservice das urbane Umfeld in eine "nachhaltige Stadt" verwandeln. Doch eine genaue Untersuchung zeigt auf, dass die bereits implementierten Bike-Sharing-Systeme ihre Versprechen von Nachhaltigkeit nicht erfüllen. Es zeigt sich, dass dieses Stück Stadtmobiliar ein Produkt von oft lang etablierter Interessenkoalition zwischen der Außenwerbungsindustrie und der Gemeindepolitik sind, deren Aktivität öffentlichen Raum zu attraktiven Standorten für Aufmerksamkeitsgewinnung umwandelt. Unter Betrachtung der Werbeindustrie, die Maßnahmen zur Lenkung der Aufmerksamkeit anwendet, zeigt die Masterarbeit, dass Sinn und Zweck des Bike-Sharing-Phänomens die Erschaffung eines ästhetischen Erlebnisses ist, welches durch das Darstellen von "urbaner nachhaltiger Mobilität" die Wahrnehmung von urbanem Raum und Leben transformieren soll.

Within the last decade, the urban phenomenon bike-sharing has colonised cities' streets on a global scale. Presented as an individual-collective sustainable mobility service, the transportation effects of bike-sharing schemes are said to change urban environments into sustainable cities . Yet, a careful examination first notices that implemented bike-sharing services do not fulfil their sustainability promise. Second, it shows that they are actually the product of often long-established coalitions of interest between the outdoor advertising industry and municipalities, and whose action turns public space into attractive sites of public promotion. Considering in addition that advertisers have seized the techniques of the happening and other perception altering artistic innovations of the 1960s to operate them into their economic management of human attention, this master thesis suggests that the raison d'être of the bike-sharing phenomenon lies in its provision of an aesthetic experience transforming the perception of urban space and life by performing urban sustainable mobility .
Keywords: Individualverkehr; Fahrradverkehr; Mobilität; Stadtverkehr; Stadtbild; Stadtraum; Stadtgestaltung; Fahrrad; Radverkehrsplanung; Radverkehrspolitik; Nachhaltigkeit; Bike-Sharing; Fahrradverleih; Fahrradverleihsystem; Öffentliches Fahrradverleihsystem